Our commercial relations with spanish america - Wright, Alfred Orin (My University, 1891)
Introduction: In speaking of Spanish America I shall refer to Mexico, Central America and all of South America, notwithstanding there are places in this vast area which the Spaniards never firmly held and where the Spanish language is not now spoken. The relation which exists between the United States of America and Spanish America is, in many respects very intimate. They form most of the land surface of one of the two great divisions of the earth, the Western Hemisphere, and are connected by a single chain of mountains extending north and south through the enters territory, thus forming a single backbone for the United States of America and Spanish America. From a historical standpoint they are also intimately connected. They both date their discovery from 1492 when Columbus landed at San Salvador. After that they were both explored and occupied by Europeans and became subject to European rule. But here appears a difference. The United States of America was occupied mainly by an energetic industrious people, leaving an oppressive government to seek for themselves a new home. Although they were under the dominion of Great Britain for more than a century and a half, they always enjoyed more or less of political freedom, and were allowed to a limited extent, all the rights of Englishmen.
Citation: Wright, Alfred Orin. Our commercial relations with spanish america. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Spanish America; Exploration; Columbus; Colonization; Commercialism; Theses; Manuscripts (documents)